Non-compliance with COVID-19-related public health measures among young adults in Switzerland: Insights from a longitudinal cohort study - Nivette, Amy; Ribeaud, Denis; Murray, Aja; Steinhoff, Annekatrin; Bechtiger, Laura; Hepp, Urs; Shanahan, Lilly; Eisner, Manuel (Social science & medicine (1982), 2021)
Adolescents and young adults were identified internationally as a group with potentially low compliance rates with public health measures aimed at curbing the spread of coronavirus disease 2019 (COVID-19). Although non-compliance research during pandemics has typically focused on concurrent correlates, less is known about how prior social and psychological risk factors are associated with non-compliance during pandemics. This paper leverages a prospective-longitudinal cohort study with data before and during the pandemic to describe patterns of non-compliance with COVID- 19 related public health measures in young adults and to identify which characteristics increase the risk of non-compliance. Data came from an ongoing cohort study in Zurich, Switzerland (n=737). Non-compliance with public health measures and concurrent correlates were measured at age 22. Antecedent sociodemographic, social, and psychological factors were measured at ages 15-20. Young adults generally complied with COVID-19 public health measures, although non-compliance with some measures (e.g., cleaning/disinfecting mobile phones, standing 1.5-2 meters apart) was relatively higher. Non-compliance, especially with hygiene-related measures, was more prevalent in males, and in individuals with higher education, higher SES, and a nonmigrant background. Non-compliance was higher in young adults who had previously scored high on indicators of “antisocial potential,” including low acceptance of moral rules, pre-pandemic legal cynicism, low shame/guilt, low self-control, engagement in delinquent behaviors, and association with delinquent peers. Young adults with low trust, including in the government’s measures for fighting the virus, also complied less. In order to increase voluntary compliance with COVID-19 measures, public health campaigns should implement strategies that foster moral obligation and trust in authorities, or leverage trustworthy individuals in the community to disseminate information. For young adults with low self-control, self-monitoring, environmental restructuring, or nudging may increase compliance. Long-term investments into integrating youth with antisocial potential into society may decrease rule-breaking behaviors, including during pandemics when compliance saves lives. •Swiss men were less likely to comply with COVID-19 public health measures than women.•Pre-pandemic factors were associated with COVID-19 non-compliance.•Factors related to “antisocial potential” were associated with non-compliance.•Moral disengagement from COVID-19 rules was strongly associated with non-compliance.•Low trust in Swiss authorities was associated with non-compliance.